Improving of Paraffin Wax Properties by Adding of Low Density Polyethylene (LDPE) - Siham Mezher Yousif; Intisar Yahiya Mohammed; Salma Nagem Mouhy (Wasit Journal of Engineering Sciences)
Petroleum wax is a polymer completely similar to ethylene with a high degree of crystalline and linearity. The method of mixing polymer with wax is one of the most common methods used in the field of improving the specifications of polymeric materials and making them widely used in various industrial fields. By mixing wax with different proportions of the polymer, to obtain better specifications in terms of solubility, hardness, thermal stability, and chemical resistance. Thus, it can be used in the electrical industries. This study examines some characteristics of the prepared wax such hardness, melting point, ash percentage, and electrical conductivity.